Effect of various dosages of Ralgro® in the suckling period on weight gain during the growing period - Simms, D.D.; Boyd, G.; Higgins, James J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We studied how implanting with various dosages of Ralgro® during the suckling period affected gains in the growing period. Preweaning performance was reported in the 1985 Cattlemen's Day Report. All calves, regardless of suckling period treatment, received 36 mg Ralgro® at the start of the growing period. Average daily gains during the growing period were similar for all treatments. Consequently, the added weight obtained from the suckling-period implants was still present at the end of the growing period.
Keywords: Beef; Ralgro®; Preweaning performance; Weight gain